Microencapsulation of Paraffin Wax in Melamine-Formaldehyde for use in Thermal Management Study - Pawar, S.S.; Suryanarayana, C.; Samui, A.B. (Journal of Research Updates in Polymer Science, 2021)
Melamine formaldehyde microcapsules containing paraffin wax as phase change material (PCM) were synthesized. Free space was generated in-situ inside microcapsules. These were characterized by FTIR Spectrophotometer, Scanning electron microscope (SEM), Differential Scanning colorimeter (DSC), and optical microscope. It was confirmed that PCM was successfully encapsulated inside the shell material. Encapsulated PCM showed good phase change properties during heating and cooling. Enthalpy value of about 100 J/g was observed. The shape of the microcapsule, showing rough morphology is expected to help during processing and crystallization. It has been experimentally confirmed that no leakage occurs during the melting of PCM. Effectiveness in temperature control in a hot environment was also found to be satisfactory.